Effect of the EGFR density of breast cancer cells on nuclear importation, in vitro cytotoxicity, and tumor and normal-tissue uptake of [111In]DTPA-hEGF. - Hu, M; Scollard, D; Chan, C; Chen, P; Vallis, K; Reilly, R (2007)
INTRODUCTION: Our objective was to evaluate the effect of epidermal growth factor receptor(s) (EGFR) density on the importation and nuclear localization of 111In-labeled diethylenetriaminepentaacetic acid human epidermal growth factor ([111In]DTPA-hEGF) in breast cancer (BC) cells in vitro and in tumor xenografts and normal tissues in vivo in athymic mice, as well as on its cytotoxicity and tumor and normal-tissue distribution. METHODS: The internalization and nuclear importation of [111In]DTPA-hEGF were measured in MCF-7, MDA-MB-231, BT-474 and MDA-MB-468 BC cells (10(4), 2 x 10(5), 6 x 10(5) and 10(6) EGFR/cell, respectively). The molecular size (Mr) distribution and immunoreactivity of nuclear radioactivity were characterized. Tumor and normal-tissue uptake of [111In]DTPA-hEGF in athymic mice implanted subcutaneously with BC xenografts were compared. Nuclear radioactivity in the tumor, lungs, liver, kidneys, spleen and colon was measured. RESULTS: There was a direct association between EGFR density and the nuclear localization of [111In]DTPA-hEGF in BC cells; nuclear importation approached saturation at 6 x 10(5) EGFR/cell. Almost all nuclear radioactivities exhibited an Mr of >100 kDa; immunoreactivity with anti-hEGF, anti-EGFR and anti-importin beta 1 antibodies was detected. The efflux of nuclear radioactivity was slowest for MDA-MB-468 cells. Cytotoxicity was correlated with EGFR expression. Uptake was greater in MDA-MB-468 than in MCF-7 xenografts and improved with preinjection of a 100-fold excess of unlabeled DTPA-hEGF. Nuclear importation was higher in liver, kidney and spleen cells than in tumor cells. CONCLUSION: [111In]DTPA-hEGF is translocated to the nucleus of BC cells complexed with EGFR and importin beta1. Nuclear importation and cytotoxicity are effected by EGFR density. The absence of hepatic and renal toxicities in [111In]DTPA-hEGF cannot be explained by a low efficiency of nuclear importation.